2002
DOI: 10.1038/nbt760
|View full text |Cite
|
Sign up to set email alerts
|

Starch content and yield increase as a result of altering adenylate pools in transgenic plants

Abstract: Starch represents the most important carbohydrate used for food and feed purposes. With the aim of increasing starch content, we decided to modulate the adenylate pool by changing the activity of the plastidial adenylate kinase in transgenic potato plants. As a result, we observed a substantial increase in the level of adenylates and, most importantly, an increase in the level of starch to 60% above that found in wild-type plants. In addition, concentrations of several amino acids were increased by a factor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 31 publications
8
128
0
2
Order By: Relevance
“…Detailed biochemical characterization revealed that this was due to regulation of the activation state of the first committed step of starch synthesis that is catalyzed by AGPase (Centeno et al, 2011). Intriguingly, however, this is not the first study to implicate reactions beyond the direct pathway of starch biosynthesis, since the mitochondrial NAD-ME (Jenner et al, 2001), the plastidial adenylate kinase (Regierer et al, 2002), and the cytosolic UMP synthase have been demonstrated to In our previous studies, we focused on mitochondrial reactions of the TCA cycle, and here, we evaluated the effect of modifying malate-pyruvate balances at different subcellular locations in a fruit ripening-specific manner by silencing either cytosolic PEPCK or the plastidic NADP-ME.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed biochemical characterization revealed that this was due to regulation of the activation state of the first committed step of starch synthesis that is catalyzed by AGPase (Centeno et al, 2011). Intriguingly, however, this is not the first study to implicate reactions beyond the direct pathway of starch biosynthesis, since the mitochondrial NAD-ME (Jenner et al, 2001), the plastidial adenylate kinase (Regierer et al, 2002), and the cytosolic UMP synthase have been demonstrated to In our previous studies, we focused on mitochondrial reactions of the TCA cycle, and here, we evaluated the effect of modifying malate-pyruvate balances at different subcellular locations in a fruit ripening-specific manner by silencing either cytosolic PEPCK or the plastidic NADP-ME.…”
Section: Discussionmentioning
confidence: 99%
“…The levels and recoveries of hexose phosphates and 3PGA were determined spectrophotometrically as detailed by Gibon et al (2002)-recoveries were 94%, 92%, and 91% for Glc 6-phosphate, Fru 6-phosphate, and Glc 1-phosphate, respectively. Inorganic phosphate content was determined as described by Lytovchenko et al (2002), and the levels of nucleotides and nucleosides were determined using the HPLC protocol defined by Regierer et al (2002). The relative levels of organic acids were determined using a GC-MS protocol as described by Roessner et al (2001a).…”
Section: Metabolite Analysismentioning
confidence: 99%
“…In addition, considerable control has been demonstrated to be harbored by the plastidial adenylate and Glc-6-P transporter (Tjaden et al, 1998;Zhang et al, 2008), with a minor yet considerable proportion also vested in the plastidial phosphoglucomutase reaction . Studies beyond the direct pathway of starch biosynthesis also indicate important roles for the mitochondrial NADmalic enzyme (Jenner et al, 2001) and the plastidial adenylate kinase (Regierer et al, 2002). However, although the exact mechanism underlying this link in the former case has yet to be resolved, the latter has been characterized to affect both the substrate levels and activation status of the AGPase reaction (Oliver et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Of these reactions, although some of the control of starch synthesis resides in the plastidial phosphoglucomutase reaction (Fernie et al, 2001b), the AGPase reaction harbors the highest proportion of control within the linear pathway (Sweetlove et al, 1999;Geigenberger et al, 1999Geigenberger et al, , 2004. In addition, considerable control resides in both the Glc-6-P phosphate antiporter (Zhang et al, 2008) and the amyloplastidial adenylate transporter (Tjaden et al, 1998;Zhang et al, 2008) as well as in reactions external to the pathways, such as the amyloplastidial adenylate kinase (Regierer et al, 2002), cytosolic UMP synthase (Geigenberger et al, 2005), and mitochondrial NAD-malic enzyme (Jenner et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation